Water extract of Armillaria mellea (Vahl) P. Kumm. Alleviates the depression-like behaviors in acute- and chronic mild stress-induced rodent models via anti-inflammatory action. (30th January 2021) - Lin, Yu-En; Wang, Hsiang-Lan; Lu, Kuan-Hung; Huang, Yun-Ju; Panyod, Suraphan; Liu, Wei-Ting; Yang, Shu-Hui; Chen, Mei-Hsing; Lu, Yun-Shen; Sheen, Lee-Yan
Abstract: Ethnopharmacology relevance: Armillaria mellea (Vahl) P. Kumm. (AM) is an edible mushroom that has been reported as treatment for several neurological disorders, such as dizziness and epilepsy in Asia. Importantly, AM shares a symbiotic relationship with Gastrodia elata Blume (GE), a medicinal herb with antidepressant-like properties. Researchers believe that AM may possess pharmacological properties similar to GE due to their symbiosis, however, few studies have investigated the pharmacological effect of AM. Aim of the study: The aim of this study was to explore the potential of AM as an antidepressant in forced-swimming test (FST) and unpredictable chronic mild stress (UCMS) rodent models and investigate its possible underlying mechanism. Materials and methods: Rats were orally administrated with 250, 500, and 1000 mg/kg body weight (bw) water extract of AM (WAM) for 28 and 35 consecutive days prior to the FST and UCMS protocols, respectively. The cerebral serotonin (5-HT) and the metabolites in the frontal cortex of rats were measured. The brain was dissected and the blood was collected to investigate the levels of inflammatory-related signaling pathway. Results: All doses of WAM reduced the immobility time in the FST without disturbing autonomic locomotion. All doses of WAM prevented stress-induced abnormal behaviors in the UCMS model, including decreased sucrose preference and hypoactivity. 500 and 1000 mg/kg bw WAM attenuated the stress-induced increases in IL-1β and TNF-α in the serum and cerebrum. 1000 mg/kg bw WAM alleviated brain inflammation by reducing the protein expression of ionized calcium binding adaptor molecule 1. Conclusion: WAM exhibited acute and chronic antidepressant-like effects, and may result from the anti-inflammatory actions. Therefore, the development of AM as a dietary therapy or adjuvant for depression treatment should be considered. Graphical abstract: Image 1 Highlights: Water extract of Armillaria mellea (WAM) reduced the immobility time in the FST. WAM rescued the down-regulated sucrose preference index induced by UCMS. WAM improved the total traveled distance and crossing events in the open field test. WAM attenuated TNF-α and IL-1β signaling induced by UCMS in serum and the cerebrum.